Utilizing flexible working arrangement into organizational citizenship behavior: a double mediation model - Noermijati, Noermijati; Farhiya, Daniyatul; Kurniawati, Desi Tri; Rosita, Ferrial; Masyhuri, Masyhuri (Business, Management and Economics Engineering, 2025)
Purpose – The current study aimed to investigate the role of career cushioning and work-life balance (WLB) as mediators in the effect of flexible work arrangements (FWA) on organizational citizenship behavior (OCB). Research methodology – Data were collected from 270 employees working in different multi-financial companies. To test the hypotheses, this study employed SEM-PLS. Findings – The results indicate that flexible working arrangement is a key factor to foster organizational citizenship behavior. Subsequently, the study highlights the importance role of career cushioning and work life balance as the mediator. Research limitations – This research was carried out on the multi-financial sector in one country and specific generation, thus, the findings’ generalization is lacking. Practical implications – This study suggested that companies or human resource teams pay attention to career cushioning and work-life balance to encourage OCB through FWA policy for millennial and Generation Z employees. Originality/Value – The uniqueness of the Millennials and Generation Z presents a complex challenge, particularly for multi-financial companies. Therefore, it is essential to establish clear career levels and ensure a balance between personal and work life. Empirical research that explores the implication of flexible working arrangement in fostering organizational citizenship in specific generation is lacking, reported solely on manufacturing companies and across generations. Meanwhile, the multi-financial sector, especially in developing countries, is understudied. Consequently, the initial study leads the examination of flexible working arrangements’ role in fostering organizational citizenship behavior in millenial and Z Generation.